2023
DOI: 10.3389/ijph.2023.1605824
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delayed and Late Initiation of Antiretroviral Therapy Among Patients With HIV in Beijing, China, 2010–2020

Abstract: Objectives: To determine factors associated with late and delayed antiretroviral therapy (ART) initiation in China and provide evidence for HIV prevention.Methods: Logistics regression model was used to determine factors associated with three outcomes: late (CD4 cell count <200 cells/µL or clinical AIDS diagnosis prior to ART initiation), delayed (more than 1 month between HIV diagnosis date and ART initiation) and either late or delayed ART initiation.Results: Multivariable analysis revealed that male,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Although marital status was not statistically significantly associated with TTAT-initiation in the present study, the predictor has been established as an independent factor elsewhere [44] with reports that being married is associated with lower risk of late ART-initiation [109]. The Iran study exploring factors associated with late ART-initiation observed that being single was associated with late ART start by 80% (aOR: 1.8, 95%CI:1.17-2.78) [103] as was also reported in China [104]. This study also found that dependency on guardian escort was 9% negatively associated with early ART-initiation.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Although marital status was not statistically significantly associated with TTAT-initiation in the present study, the predictor has been established as an independent factor elsewhere [44] with reports that being married is associated with lower risk of late ART-initiation [109]. The Iran study exploring factors associated with late ART-initiation observed that being single was associated with late ART start by 80% (aOR: 1.8, 95%CI:1.17-2.78) [103] as was also reported in China [104]. This study also found that dependency on guardian escort was 9% negatively associated with early ART-initiation.…”
Section: Discussionsupporting
confidence: 73%
“…The current study finding on younger age Vs TTAT are in congruent with West African multinational study reported that younger age (of at least 24 years) was associated with early ART-initiation [94] – a similar association was also observed from South African KwaZulu Natal study [102]. The KwaZulu Natal study reported that early mid-age (of 35-44 years) had a 63% positive association with early ART-initiation (in males) and 90% probability (in females) whereas being ≥45 years old was a barrier to early ART-initiation [102] – the findings also shared in a study from Iran where old age was reported to be significantly associated with risk of late ART-initiation [aOR:1.02, 95%CI:(1.00-1.04)] [103] and a similar pattern was also observed from China [104].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This pattern could result from underlying factors, including low perception of and misconceptions regarding transmission risks, stigma and subsequent underreporting of transmission from MSM, along with poor risk assessment and sexual history collection by healthcare providers [28]. Late initiation of ART was defined as having CD4 counts <200 cells/μl or having a clinical AIDS diagnosis at ART initiation [29]. The proportion with CD4 counts <200 cells/μl significantly decreased from 2010 to 2013 among PLWH in older and younger groups, and delayed initiation of ART significantly improved from 2014 to 2020 for both groups.…”
Section: Discussionmentioning
confidence: 99%